Digital Storytelling Review in a Pharmacy Self-Care Course - Jenna M. Mills; Jason W. Guy; Julie H. Oestreich (MDPI AG, 2022)
Digital storytelling is a type of active learning that allows instructors to simulate real-life situations through a series of connected videos. While this technique has been used in other healthcare education disciplines, its use in pharmacy has not been well documented. A digital storytelling model was incorporated in a required self-care pharmacy course to assess if the technique was helpful to improve the knowledge, confidence, and satisfaction of students. Due to a shift in online learning, the self-care course offered a remote exam review session containing a digital storytelling model, and this approach was compared to an in-person exam review that followed a lecture-based model held earlier in the course. Pre- and post-knowledge assessments were given to determine the impact of the digital storytelling review. There were 50 students involved in both sessions and there was a 70% response rate in the digital storytelling group and a 90% response rate in the lecture-based group. Students' knowledge numerically improved, but not to a statistically significant level for most questions. Nonetheless, students reported more confidence (p < 0.05) in their ability to pass the upcoming exam following the digital storytelling review. Thematic analysis revealed that the digital storytelling session was engaging and interactive, though time-management and breakout rooms could be further optimized. Based on these results, exam review in a required self-care pharmacy course using a digital storytelling format may be a suitable method for students to apply course content and may particularly be of utility in online or hybrid courses.